?EXTRACTION AND CHEMICAL QUALITY CHARACTERISTICS EVALUATION OF ORANGE PEEL PECTIN (Biological Sciences - PJSIR, 2003)
Optimum conditions for the extraction and precipitation of pectin from orange peels were investigated. Changes in pH, temperature and extraction time, significantly, affected the extraction of pectin. Maximum pectin yield was 17.7%, which was obtained on soaking finely ground orange peels in sulphuric acid solution of pH 2.5 at 80°C for 120 min. Maximum pectin was precipitated from the extract by adding 95% ethanol at the rate of 200ml/l. Anhydrogalacturonic acid and methoxyl contents of pectin obtained under these optimum extraction conditions were 72.80% and 9.77% respectively, while equivalent weight value was 943. These chemical characteristics values were within the accepted limit of good quality pectin.